Situated Analytics: Demonstrating immersive analytical tools with Augmented Reality. (October 2016) - ElSayed, Neven A.M.; Thomas, Bruce H.; Marriott, Kim; Piantadosi, Julia; Smith, Ross T.
Abstract: This paper introduces the use of Augmented Reality as an immersive analytical tool in the physical world. We present Situated Analytics, a novel combination of real-time interaction and visualization techniques that allows exploration and analysis of information about objects in the user's physical environment. Situated Analytics presents both situated and abstract summary and contextual information to a user. We conducted a user study to evaluate its use in three shopping analytics tasks, comparing the use of a Situated Analytics prototype with manual analysis. The results showed that users preferred the Situated Analytics prototype over the manual method, and that tasks were performed more quickly and accurately using the prototype.